Thyroid function status in patients with thyroid associated ophthalmopathy: a study for Nepal - Piya, Saurav; Gurung, Jeena; Khatri, Anadi (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Introduction: Thyroid Eye Disease (TED) is an organ-specific autoimmune inflammatory incapacitating eye disorder usually associated with Graves’ disease affecting the orbit. Objectives: To determine thyroid function status in patients with thyroid-associated Ophthalmopathy.Methods: This is a hospital-based cross-sectional study of sixty three clinically diagnosed new cases of thyroid-associated ophthalmopathy done at Nepal Eye Hospital, Kathmandu from February 2012 to January 2013. Detailed history, systemic & ocular examination with special emphasis on evaluation of extraocular movement, lid signs, exophthalmos with Hertel's exophthalmometer was done. Thyroid function test and endocrine consultation were also done in all cases.Results: There were an equal distribution of TED with hyperthyroid (34.95%) and euthyroid status (34.95%). The most common presentation of both euthyroid and hypothyroid patient was tremor (13.4%) and palpitation (13.45%). The most common symptom of TED was foreign body sensation (54 %) but in TED with euthyroid and hypothyroid status, redness (22.2 %) and diminution of vision (20.6 %) were more frequent symptoms respectively. The most common presenting sign was Von Graefe’s sign (69 %). Among TED with hyperthyroid and hypothyroid status, Dalrymple's sign (29.3%) and Mobius sign (17.4%) were most common respectively.Conclusion: Thyroid-associated ophthalmopathy is an important health concern among patients with a thyroid disorder. TED with hyperthyroid states present more severely than hypothyroid and euthyroid states. As TED occurred with a high prevalence in all thyroid states, a close collaboration between endocrinologists and ophthalmologists along with timely referrals of patients with any eye complaint is mandated.